Heat Conduction Characteristics of Vertically Aligned Single-Walled Carbon Nanotubes Measured by Raman Spectroscopy - BADAR, Saifullah; ISHIKAWA, Kei; HORI, Takuma; XIANG, Rong; THURAKITSEREE, Theerapol; CHIASHI, Shohei; WATANABE, Makoto; SHIOMI, Junichiro; MARUYAMA, Shigeo (Nihon Kikai Gakkai rombunshuu. B hen, 2013)
In this work, the film thermal conductivity and the film-substrate interfacial thermal contact resistance of vertically-aligned single-walled carbon nanotube (VA-SWNT) films were measured with a proposed method utilizing temperature dependence of Raman spectrum. The proposed method harnesses the excitation laser power of the Raman spectroscopy to heat the VA-SWNT films synthesized on a silicon substrate by alcohol catalytic chemical vapor decomposition (ACCVD) method, and measures film temperature from the Raman spectrum. A relationship between the input laser heat and the measured temperature is modeled with a detailed heat conduction equation, and its numerical solutions were compared with the experimentally measured results to extract the film thermal conductivity and the film-substrate interfacial thermal contact resistance. The method found the thermal conductivity of the VA-SWNT film to be around 2 Wm-1K-1 and the film-substrate interfacial thermal contact resistance to be around 2×10-6 m2KW-1. The obtained film thermal conductivity corresponds to the thermal conductivity equivalent of an individual SWNT of several tens of Wm-1K-1. This value was more than an order of magnitude smaller than the values reported on individual SWNTs.